KONSEP KYOUIKU PAPA PADA TOKOH AYAH DALAM SERIAL DRAMA JEPANG JUKEN NO KAMISAMA KARYA SUTRADARA IWAMOTO HITOSHI - NURCAHYANTI, - (Jurnal Ilmiah Mahasiswa FIB, 2014)
This thesis discusses the concept of kyouiku papa in Japanese society. The concept kyouiku papa is how fathers get involved in taking care of and educatingchildren. In the present study, the author use data sources in the form of a drama series entitled Juken no Kamisama. This drama tells the story of the father who strive to provide the best education for their children. Father has done various thing in order to give the best education for his children. This study uses sociological approach by Ian Watt. He said that literatureas a reflection of society. To help the author for analyzing this drama , the authoralso uses the concept of kyouiku papa in Japanese society as well as the theory of Mise en Scene. The results of this study indicate that there are three fathers figuresdepicting a father who runs the concept kyouiku papa. Third father in the play not only perform its role as a breadwinner , but also involved in the nurturing and attention to his children's education . The author also find ways that is done by father giving the best education for his son. The author suggests that further research may examine this drama by usinga different approach . For example, by examining the role of mothers in parenting in today's era of Japanese society . Keywords : Kyouiku Papa , Fathers , Sociology , Drama Series , Society of Japan